Rancang Bangun Aplikasi Pengelolaan Surat Masuk Dan Surat Keluar Pada Pengadilan Tinggi Surabaya - Yusuf Bagus Anggara; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Letter is an important document in Surabaya High Court because it supports the business process activities Surabaya High Court. Therefore, the data must be complete mailing, distribution and storage should be timely letter should be well ordered. The conditions at the Surabaya High Court incomplete data writing letters, distributing archives are often delayed because of the long groove applies a system or procedure is too complicated. To solve this problem, so the storage and recording of the letter needs to be converted into digital data and computerized. To meet these needs it is necessary to be made application mail handling incoming and outgoing mail at the Surabaya High Court. Stages of making this application begins with communication, planning, modeling, construction, and operation. Once tested, the application management of incoming and outgoing letter can handle the recording process incoming letter, handle the disposition of incoming letter, handle the process of making a number of outgoing letter as well as recording your outgoing letter so, can generate data incoming letter, the data disposition, the data outgoing letter, and several reports including archiving reports, statements disposition, disposition tracking reports, and reports of outgoing letter.